Knowledge and attitude towards cadaveric organ donation among Filipinos - Tan, Guia C.
Current ethical controversies surrounding living organ donation in the country prompted an investigation into the more ethical alternative of securing donations from deceased donors. Data from the unpublished 2005 Nationwide Survey on People's Knowledge and Opinions about Organ Donation involving 2140 individuals aged 18-65 were subjected to statistical analysis to find out what the knowledge and attitude of Filipinos are towards cadaveric organ donation. It was found that a significant majority (78%) were willing to be deceased donors and that the general beliefs of the studied population were favorable towards the practice. Significant factors that predisposed to donation were the person's knowledge that organ donation does not cause pain to the deceased donor, exposure to donation through radio, movies, television alone or in combination with print media--newspapers, books, magazines, leaflets, brochures and more specific knowledge about transplants--such as which organs could be donated and when they could be donated. Being of the Muslim faith was noted to make a person less inclined to donate as well as being 40-49 or 60-65 years of age, and knowing the correct definition of brain death. Based on the findings, strategies for increasing cadaveric organ donation were suggested which included the use of non-print media and the recruitment of people from the entertainment industry, the highlighting of the fact that organ donation does not cause pain to the deceased and the early training of medical and paramedical personnel which includes correcting mistaken perceptions that filipinos are not open to donation or believe it is mutilating. The findings of this paper support the pursuit of optimizing donation from the deceased to answer the current shortage of transplantable organs.